Systematic development of a theory-informed multifaceted behavioural intervention to increase physical activity of adults with type 2 diabetes in routine primary care: Movement as Medicine for Type 2 Diabetes. (December 2015) - Avery, Leah; Charman, Sarah; Taylor, Louise; Flynn, Darren; Mosely, Kylie; Speight, Jane; Lievesley, Matthew; Taylor, Roy; Sniehotta, Falko; Trenell, Michael
Abstract Background Despite substantial evidence for physical activity (PA) as a management option for type 2 diabetes, there remains a lack of PA behavioural interventions suitable for delivery in primary care. This paper describes the systematic development of an evidence-informed PA behavioural intervention for use during routine primary care consultations. Methods In accordance with the Medical Research Council Framework for the Development and Evaluation of Complex Interventions, a four-stage systematic development process was undertaken: (1) exploratory work involving interviews and workshop discussions identified training needs of healthcare professionals and support needs of adults with type 2 diabetes; (2) a systematic review with meta- and moderator analyses identified behaviour change techniques and optimal intervention intensity and duration; (3) usability testing identified strategies to increase implementation of the intervention in primary care and (4) an open pilot study in two primary care practices facilitated intervention optimisation. Results Healthcare professional training needs included knowledge about type, intensity and duration of PA sufficient to improve glycaemic control and acquisition of skills to promote PA behaviour change. Patients lacked knowledge about type 2 diabetes and skills to enable them to make sustainable changes to their level of PA. An accredited online training programme for healthcare professionals and a professional-delivered behavioural intervention for adults with type 2 diabetes were subsequently developed. This multifaceted intervention was informed by the theory of planned behaviour and social cognitive theory and consisted of 15 behaviour change techniques. Intervention intensity and duration were informed by a systematic review. Usability testing resolved technical problems with the online training intervention that facilitated use on practice IT systems. An open pilot study of the intervention with fidelity of delivery assessment informed optimisation and identified mechanisms to enhance implementation of the intervention during routine diabetes consultations. Conclusions Movement as Medicine for Type 2 diabetes represents an evidence-informed multifaceted behavioural intervention targeting PA for management of type 2 diabetes developed for delivery in primary care. The structured development process undertaken enhances transparency of intervention content, replicability and scalability. Movement as Medicine for Type 2 diabetes is currently undergoing evaluation in a pilot RCT. Trial registration ISRCTN67997502